Utilization of Pitali (Trewia nudiflora) for Manufacturing Commercial Plywood in Bangladesh - Shahria, M Hasan; Ashaduzzaman, M; Shams, M Iftekhar; Sharmin, Arifa; Islam, M Muktarul (Bangladesh Journal of Scientific and Industrial Research, 2009)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> The study was conducted to find out the potentiality of Pitali (Trewia nudiflora) for manufacturing commercial plywood and evaluating its physical and mechanical properties. Two 9-ply plywood of 2.4m x 1.2m x 18mm size were manufactured using liquid urea formaldehyde adhesive. The physical and mechanical properties of T. nudiflora plywood were compared with the existing market available plywood manufactured by Simul (Bombax ceiba). It was found that density were 509.82 kg/m3 and 490.96 kg/m3, moisture content after curing were 10.67% and 17.61%, thickness swelling were 6.90% and 7.29%, linear expansion were 0.19% and 0.15%, water absorption were 50.89% and 64.79%, MOR were 29.94 N/mm2 and 27.05 N/mm2, MOE were 1613.89 N/mm2 and 1160.68 N/mm2, and tensile strength were 14.75 N/mm2 and 13.12 N/mm2 for T. nudiflora plywood and market plywood respectively. The evaluated physical and mechanical properties of T. nudiflora plywood were also compared with some relevant results and standards reported earlier. Key Words: Plywood, Trewia nudiflora, Physical properties, Mechanical properties. doi: 10.3329/bjsir.v43i4.2249 Bangladesh J. Sci. Ind. Res. 43(4),581-587, 2008